Existence of Global Solution and Traveling Wave of the Modified Short-Wave Equation - Hyungjin Huh (Advances in Mathematical Physics)
The modified short-wave equation is considered under periodic boundary condition. We prove the global existence of solution with finite energy. We also find traveling wave solutions which is the form of elliptic function.